Food enrichment with omega-3 fatty acids - Jacobsen, Charlotte; Nielsen, Nina Skall; Horn, Anna Frisenfeldt; Sørensen, Ann-Dorit Moltke (Woodhead Publishing in food science, technology, and nutrition, 2013)
Omega-3 fatty acids provide many health benefits, from reducing cardiovascular disease to improving mental health, and consumer interest in foods enriched with omega-3 fatty acids is increasing. Formulating a product enriched with these fatty acids that is stable and has an acceptable flavour is challenging. Food enrichment with omega-3 fatty acids provides an overview of key topics in this area. Part one, an introductory section, reviews sources of omega-3 fatty acids and their health benefits. Chapters in part two explore the stabilisation of both fish oil itself and foods enriched with omega-3 fatty acids. Part three focuses on the fortification of different types of foods and beverages with omega-3 fatty acids, including meat products, by the modification of animal diets and other methods, infant formula and baked goods. Finally, part four highlights new directions in the field and discusses algal oil as a source of omega-3 fatty acids and labelling and claims in foods containing omega-3 fatty acids. Food enrichment with omega-3 fatty acids is a standard reference for professionals in the functional foods industry involved with research, development and quality assessment and for researchers in academia interested in food lipids, oxidation and functional foods. Provides a comprehensive overview of formulating a product enriched with omega-3 fatty acids that is stable, provides many health benefits and has an acceptable flavourReviews sources of omega-3 fatty acids and their health benefits and explores the stabilisation of fish oil and foods enriched with omega-3 fatty acidsFocuses on the fortification of different types of foods and beverages with omega-3 fatty acids and highlights new directions in the field.